Uterine artery Doppler screening in 18 to 24 weeks of pregnancy for prediction of adverse maternal outcome (BIRDEM Medical Journal, 2023)
Background: Uterine artery Doppler velocimetry (UADV) analysis has been extensively studied in the second trimester of pregnancy as a predictive investigation for the future development of adverse feto-maternal outcome. This study was designed to assess the association between findings of uterine artery Doppler velocimetry with maternal outcome.Methods: This was a prospective observational study among the pregnant women attending the inpatient and outpatient departments of Obstetrics and Gynecology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Segunbagicha, Dhaka, from July 2021 to December 2021. A total of 31 women with singleton pregnancy were enrolled in this study at their 18-24 weeks of gestation. After obtaining informed written consent, data were collected from patients on variables of interest using a semistructured questionnaire. All the respondents underwent uterine artery Doppler velocimetry at 18 to and 24 weeks of gestation and were followed up to observe its relationship with feto-maternal outcome. Descriptive and inferential analyses were done using SPSS v.21.Results: More than half (51.6%) of the subjects belonged to 30 years and above. The mean age was found 29.71±4.8 years with ranged from 21 to 40 years. Most (96.8%) of the subjects had diabetes mellitus and only 32.3% subjects had hypertension. More than half (54.8%) had adequate diastolic flow and 32.3% subjects had diastolic notch. Majority (64.3%) of the respondents with decreased diastolic flow had preeclampsia. Majority (70.0%) of the respondents with diastolic notch also developed preeclampsia. All these findings were statistically significant (p